Reduced Neonatal Mortality in Meishan Piglets: A Role for Hepatic Fatty Acids? - Fainberg, Hernan P.; Bodley, Katherine; Bacardit, Jaume; Li, Dongfang; Wessely, Frank; Mongan, Nigel P.; Symonds, Michael E.; Clarke, Lynne; Mostyn, Alison (PLOS ONE, 2012)
The Meishan pig breed exhibits increased prolificacy and reduced neonatal mortality compared to commercial breeds, such as the Large White, prompting breeders to introduce the Meishan genotype into commercial herds. Commercial piglets are highly susceptible to hypoglycemia, hypothermia, and death, potentially due to limited lipid stores and/or delayed hepatic metabolic ability. We therefore hypothesized that variation in hepatic development and lipid metabolism could contribute to the differences in neonatal mortality between breeds. Liver samples were obtained from piglets of each breed on days 0, 7, and 21 of postnatal age and subjected to molecular and biochemical analysis. At birth, both breeds exhibited similar hepatic glycogen contents, despite Meishan piglets having significantly lower body weight. The livers from newborn Meishan piglets exhibited increased C18∶1n9C and C20∶1n9 but lower C18∶0, C20∶4n6, and C22∶6n3 fatty acid content. Furthermore, by using an unsupervised machine learning approach, we detected an interaction between C18∶1n9C and glycogen content in newborn Meishan piglets. Bioinformatic analysis could identify unique age-based clusters from the lipid profiles in Meishan piglets that were not apparent in the commercial offspring. Examination of the fatty acid signature during the neonatal period provides novel insights into the body composition of Meishan piglets that may facilitate liver responses that prevent hypoglycaemia and reduce offspring mortality.